PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK-EMKM DENGAN APLIKASI AKUNTANSI UKM - Novie Astuti Setianingsih; Wiwiek Kusumaning A; Atik Tri Andari; Elmi Rahma Aalin; Eti Putranti (Universitas Mataram, 2023)
Micro entrepreneurs have problems in compiling financial reports because business income is still mixed with household needs. This happens because of the lack of accounting knowledge and time constraints, activities are needed to assist the use of smartphone-based accounting applications with the SME Accounting application. The purpose of this community service activity is to provide training and assistance for partners regarding knowledge about making financial reports according to SAK-EMKM by using the UKM Accounting application. Training and assistance in preparing financial reports was carried out at the UMKM Cookies